Association(s) between objectively measured sedentary behavior patterns and obesity among Brazilian adolescents - Werneck, André O. [UNESP]; Silva, Evelyn C.A.; Bueno, Maria R.O.; Vignadelli, Lidyane Z.; Oyeyemi, Adewale L.; Romanzini, Catiana L.P.; Ronque, Enio R.V.; Romanzini, Marcelo (Human Kinetics, 2019)
Purpose: To investigate the association between patterns of sedentary behavior and obesity indicators among adolescents. Methods: This was a cross-sectional study conducted among 389 adolescents (186 boys) aged 10–14 years. Body mass index, body fat (skinfolds), and waist circumference were adopted as outcomes. Sedentary behavior patterns (total time, bouts, and breaks) measured through accelerometry (GT3X and GT3X+; ActiGraph, Pensacola, FL) were adopted as exposures. Peak height velocity, moderate to vigorous physical activity (accelerometer), cardiorespiratory fitness (Léger test), sex, and chronological age were adopted as covariates. Linear regression models adjusted for covariates were used to determine associations between outcome and exposure variables. Results: The mean age of adolescents was 11.8 (0.7) years. Boys were more active than girls (P < .001). Accumulating shorter bouts (1–4 min) of sedentary behavior was negatively associated with body mass index (β = −0.050; 95% confidence interval [CI], −0.098 to −0.003) and waist circumference (β = −0.133; 95% CI, −0.237 to −0.028). Similarly, a higher number of breaks in sedentary behavior were negatively associated with body mass index (β = −0.160; 95% CI, −0.319 to −0.001) and waist circumference (β = −0.412; 95% CI, −0.761 to −0.064). Conclusion: Shorter bouts of sedentary behavior (1–4 min) and a higher number of breaks of sedentary behavior were associated with lower adiposity. Our findings also suggest that breaking up sedentary time to ensure bouts of sedentary behavior are short might contribute to the prevention of obesity in adolescents.
Keywords: Adiposity; Motor activity; Physical inactivity